Pengaruh Pendidikan Kewirausahaan, Pengalaman Berwirausaha, dan Motivasi Berwirausaha Terhadap Pengelolaan Usaha Tani Perkotaan - Kamaruddin, Citra Ayni (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
This research was conducted to find out how entrepreneuurship education, entrepreneuurial experience, and entrepreneuurial motivation looking for influence the management of farming in urban areas, especially in the Citra Women Farmers Group located at BTN Citra Tello Permai, Tello Baru Village, Panakkukang District, Makassar City. This research was conduucted using a quantitative approach through associative methods and using multiple linear regression data analysis techniques. The results showed that in this study: (1) the variable of entrepreneurship education had a positive and significant effect on the management of urban farming, especially in KWT Citra; (2) the entrepreneurial experience variable has a positive and significant influence on the management of urban farming, especially in KWT Citra; (3) the variable of entrepreneurial motivation partially has no positive and insignificant effect on the management of urban farming, especially in KWT Citra; (4) educational entrepreneurship, entrepreneurial experience, and entrepreneurial motivation have a simultaneous influence on the management of urban farming in KWT Citra.